Green Accounting Intervens Corporate Governance and Environmental Performance On Financial Performance - M. Imron Hamzah; Suripto; Holiawati (International Journal of Educational Administration, Management, and Leadership, 2025)
This study aims to analyze the empirical evidence of green accounting as an intervening variable in the influence of corporate governance and environmental performance on financial performance in energy sector companies listed on the Indonesia Stock Exchange during the 2021–2023 period. The research adopts a quantitative and associative approach. The population comprises 83 energy sector companies listed on the Indonesia Stock Exchange between 2021 and 2023. A purposive sampling method was applied, resulting in 53 companies over three years, yielding 159 data points. Data analysis was conducted using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results indicate that corporate governance and environmental performance have a direct, positive, and significant impact on green accounting. Furthermore, corporate governance, environmental performance, and green accounting positively and significantly influence financial performance. Green accounting acts as an intervening variable that strengthens the relationship between corporate governance, environmental performance, and financial performance. This study offers managerial implications, highlighting the importance of enhancing corporate governance, environmental performance, and the implementation of green accounting to improve financial performance and support sustainability. Future research is encouraged to expand the scope to other industrial sectors, incorporate external factors such as regulations and organizational culture, and adopt a longitudinal approach to examine the long-term impact of green accounting on corporate financial sustainability. These findings advocate for the development of standardized reporting policies and investment in environmentally friendly technologies to strengthen the connection between sustainability and financial performance.